Work decently: AI-driven marketing strategies for a competitive edge in tourism - Zaki, Karam; Abdelghani , Abdelrahman A. A.; Ahmed, Hebatallah A. M.; Abdelfadel, Tagreed; Abusalim, Entesar; Ahmed , Khalda; Abuzaid, Alaa E.; Elnagar, Ahmed K. (Research Journal in Advanced Humanities, 2025)
Artificial intelligence-driven marketing (AIM) is emerging as a vital instrument for securing competitive advantage (CA) by enabling personalized customer interactions in the dynamic hospitality and tourism sectors. In Saudi Arabia, AIM techniques offer significant potential to attract and retain customers, underscoring the sector's importance. However, research on AIM's influence on tourists' decision-making (DM), guest engagement (GE), and satisfaction in this context remains in its early stages. This study investigates how AIM strategies shape tourists' DM processes, comparing the impacts of social media platforms and hospitality e-commerce channels on GE and guest loyalty (GL). Data was collected via a structured questionnaire using convenience sampling, resulting in 323 valid responses from tourists across Riyadh, Jeddah, and Madinah. Analysis using partial least squares structural equation modeling (PLS-SEM) revealed that AIM significantly influences DM, GE, and CA. Notably, personalized interactions on social media platforms markedly enhance GL, emphasizing the need for tailored AIM strategies. This research enriches the limited literature on AIM in the Saudi hospitality sector and introduces an innovative model integrating AIM, social media engagement, and personalization strategies, providing valuable insights for both researchers and practitioners.